Calorie Labeling in a Rural Middle School Influences Food Selection: Findings from Community-Based Participatory Research - Monica Hunsberger; Paul McGinnis; Jamie Smith; Beth Ann Beamer; Jean O’Malley (Journal of Obesity)
Background. Calorie labeling at the point-of-purchase in chain restaurants has been shown to reduce energy intake. Objective. To investigate the impact of point-of-purchase calorie information at one rural middle school. Methods. With a community-based participatory research framework a mixed method approach was used to evaluate the impact of point-of-purchase calorie information. Students in grades 6–8, dining at the school cafeteria January and February 2010, participated for 17 school days each month; in January a menu was offered in the usual manner without calorie labels; the same menu was prepared in February with the addition of calorie labels at point-of-purchase. Gross calories served per student were measured each day allowing for matched comparison by menu. In March/April of 2010, 32 students who ate in the cafeteria 3 or more times per week were interviewed regarding their views on menu labeling. Results. Calorie consumption decreased by an average of 47 calories/day; fat intake reduced by 2.1 grams/day. Five main themes were consistent throughout the interviews. Conclusion. Point-of-purchase calorie labels can play a role in reducing the number of calories consumed by middle school age children at the lunch. The majority of students interviewed found the calorie labels helped them choose healthier food.